No association between hepatitis C virus infection and risk of colorectal cancer: a systematic review and meta-analysis of cohort studies - Chang, Cheng; Yan, Hong-Mei; Liao, Yan-Lin (Frontiers in Medicine, 2024)
Background and aim There is still uncertainty regarding whether hepatitis C virus (HCV) infection is associated with colorectal cancer (CRC). This study aims to investigate the potential association between HCV infection and CRC through a systematic review and meta-analysis of cohort studies. Methods PubMed, Embase, and Web of Science were systematically searched from the beginning of their inception to October 2023 to find relevant cohort studies on the association between HCV infection and CRC risk. The random-effect, generic inverse variance method was used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) for CRC outcome among individuals with HCV infection. We also performed subgroup and sensitivity analysis. Results A total of 8 cohort studies involving 1,939,164 participants were included in this meta-analysis. The result from the meta-analysis suggested that there was no statistically significant association between HCV and the risk of developing CRC (HR = 0.99, 95% CI: 0.82–1.88, p = 0.88) with low statistical heterogeneity (I2 = 28%, p = 0.20). Subgroup analyses that were conducted based on study design, diagnosis of HCV infection, and publication year yielded similar results. Analyses of subgroups based on study areas revealed that there was no significant association between HCV infection and CRC risk in Asia (n = 2, HR = 0.96, 95% CI: 0.71–1.29, p = 0.79; I2 = 26%), Europe (n = 3, HR = 1.06, 95% CI: 0.83–1.37, p = 0.63; I2 = 0%), and North America (n = 2, HR = 1.10, 95% CI: 0.87–1.38, p = 0.44; I2 = 0%); however, a negative correlation was found in Oceania (n = 1, HR = 0.43, 95% CI: 0.22–0.84, p = 0.01). Sensitivity analysis further reinforce the stability of our conclusion. Conclusion Our cohort-based meta-analysis showed insufficient evidence to support the association between HCV infection and an increased risk of CRC. To gain a clearer insight into the potential association between these two conditions, it would be beneficial to conduct large, well-designed, high-quality prospective cohort studies that consider different ethnic populations and potential confounding factors. Systematic review registration: PROSPERO, identifier [CRD42023472688], https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023472688.